Strategi Komunikasi Promosi @DesaWisataHanjeli Melalui Instagram - Hilda Sri Rahayu; Elis Yulianti; Mulfi Sandi Yuda (JIKA (Jurnal Ilmu Komunikasi Andalan), 2023)
The presence of social media cannot be separated from Indonesian society, namely with the emergence of Instagram accounts carried out as a means of tourism promotion, promotional communication strategies. influencers and content creators use Instagram social media as a means of promotion, one of which is Instagram social media @desawisatahanjeli as a means of promoting tourism in Sukabumi Regency. Based on the above background, the focus of the problem of this research is how the Instagram social media communication strategy @desawisatahanjeli in finding tourists through Instagram media promotion. This research is based on an innovative approach to tourism promotion communication strategies, namely Instagram social media. A qualitative approach will be used in this research using a case study research method. From the research findings, the use of Instagram social media as a means of promoting tourism in Sukabumi Regency uses various Instagram features such as: photo titles or captions, hashtags, comments, mentions. Furthermore, from the findings of observations of Instagram informants and interviews, @desawisatahanjeli is very effective in promoting tourism in Sukabumi District, as shown by the testimonials of visitors through the captions they uploaded on their personal social media.